2021
DOI: 10.3390/ijms222312651
|View full text |Cite
|
Sign up to set email alerts
|

Bone Biomarkers in Mucopolysaccharidoses

Abstract: The accumulation of glycosaminoglycans (GAGs) in bone and cartilage leads to progressive damage in cartilage that, in turn, reduces bone growth by the destruction of the growth plate, incomplete ossification, and growth imbalance. The mechanisms of pathophysiology related to bone metabolism in mucopolysaccharidoses (MPS) include impaired chondrocyte function and the failure of endochondral ossification, which leads to the release of inflammatory cytokines via the activation of Toll-like receptors by GAGs. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The GAGs align specifically with the CGI, increasing the ordering of the CGI fibrils in the direction of mechanical force transmission [83,84]. On the other hand, too high accumulation of GAGs in cartilage and bone tissues leads to progressive cartilage damage, reducing bone growth [86,87].…”
Section: Stages Of Biomineralisationmentioning
confidence: 99%
“…The GAGs align specifically with the CGI, increasing the ordering of the CGI fibrils in the direction of mechanical force transmission [83,84]. On the other hand, too high accumulation of GAGs in cartilage and bone tissues leads to progressive cartilage damage, reducing bone growth [86,87].…”
Section: Stages Of Biomineralisationmentioning
confidence: 99%
“…According to some authors, bone remodeling process also includes an activation phase, in which osteoclast precursor cells are activated, and after formation, follows termination phase, also known as quiescence, when osteoblasts become bone lining cells or differentiate in osteocytes [23]. The perfect equilibrium in bone remodeling is tightly connected with the action of various local and systemic factors: hormones, cytokines, chemokines, and biomechanical stimuli [24]. When formation and resorption phases are disconnected, bone disorders appear, and an imperfect balance generates serious bone disease, such as A complete cycle of bone remodeling can be divided in three main phases: first, osteoclasts set up bone resorption; second phase, entitled reversal, represents the transition between resorption and formation; and, finally, the third phase, bone formation.…”
Section: Bone Tissue Organization and Biochemistrymentioning
confidence: 99%
“…(3,4) In recent years, cytokines have also been implicated as potential prognostic biomarkers in bone disease-specifically, multiple studies have found aberrant levels of inflammatory cytokines in mucopolysaccharidosis-associated dysplasia. (5,6) The potential use of cytokines as biomarkers and targets of therapy in the management of skeletal dysplasia is intriguing. Owing in large part to their wide anatomic distribution and characteristic pleiotropism, it is often difficult to provide comprehensive description of cytokines' effects throughout the body.…”
Section: Introductionmentioning
confidence: 99%
“…( 3 , 4 ) In recent years, cytokines have also been implicated as potential prognostic biomarkers in bone disease—specifically, multiple studies have found aberrant levels of inflammatory cytokines in mucopolysaccharidosis‐associated dysplasia. ( 5 , 6 )…”
Section: Introductionmentioning
confidence: 99%